Vulnerability and self-perceived health status among light and heavy smokers: the relationship to short-term fear appeal tobacco control messages Vulnerabilidade e percepção de saúde auto-referida entre fumantes leves e pesados: a relação com mensagens anti-fumo voltadas para o apelo ao medo imediato - André Salem Szklo; Evandro Silva Freire Coutinho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
It is important to stimulate smokers to acquire some level of risk perception associated with their current behavior in order to motivate smoking cessation. The present article attempts to understand how the content of short-term fear appeal government tobacco messages may interact with different levels of daily cigarette consumption in order to affect smokers' vulnerabilities, expressed by self-perceived health status. A Poisson model was used to estimate the prevalence ratio of fair or poor self-perceived health status (FPHS) according to daily cigarette consumption. We also calculated the proportions of smokers who stated that selected health warning pictures on cigarette packets encourage people to quit smoking, stratified by self-perceived health status and daily cigarette consumption. The proportion of smokers with FPHS was 25% higher among those who smoked > 20 cigarettes/day (p = 0.01). Among smokers with FPHS, heavy smokers showed the highest proportions of responses in favor of selected warning pictures most closely related to losses in ordinary daily living, such as shortness of breath and being bothered by cigarette addiction. Short-term loss-framed tobacco control messages seem to have raised awareness of vulnerability among heavier smokers. É importante incentivar os fumantes a adquirir algum nível de percepção do risco associado ao seu comportamento atual, para motivá-los a parar de fumar. O artigo procura elucidar em que medida o conteúdo do apelo ao medo imediato contido em mensagens anti-fumo nas campanhas governamentais pode interagir com o consumo diário de cigarros, no sentido de afetar as vulnerabilidades dos fumantes, expressas pela percepção de saúde auto-referida. Um modelo de Poisson foi utilizado para estimar a razão de prevalências de percepção de saúde auto-referida regular ou ruim, segundo consumo diário de cigarros. Calculou-se também a proporção de fumantes que afirmou que mensagens anti-fumo impressas em maços de cigarros incentivam as pessoas a para de fumar, estratificada por percepção de saúde auto-referida e consumo diário de cigarros. A proporção de fumantes com percepção de saúde auto-referida regular ou ruim foi 25% maior entre aqueles que fumavam > 20 cigarros/dia (p = 0,01). Entre fumantes com percepção de saúde auto-referida regular ou ruim, os fumantes pesados apresentaram as proporções mais elevadas de respostas em favor das mensagens anti-fumo mais identificadas com perdas na vida cotidiana, como falta de fôlego e sentir-se incomodado pela própria dependência em relação ao cigarro. Mensagens anti-fumo voltadas para perdas em curto prazo parecem ter aumentado a conscientização dos fumantes mais pesados em relação à sua própria vulnerabilidade.